ڕەنگدانەوەى رێککەوتنامەى (سایس پیکۆ- سازەنۆڤ) لەسەر کوردستانی ژێر دەسەڵاتى عوسمانى 1916 - عبدولره‌حمن, پشكۆ حمه‌ تاهیر (Sulaimani Journal for Humanities, 2018)
The Reflection of Sykes-Picot-Sazanov Agreement over the Ottoman Empire's Kurdistan in 1916 In the middle of the First World War, the trials for dividing Ottoman Empire and controlling the rich and valued regions generally and Kurdistan part of Ottoman Empire in particular was an important ingredient of the diplomatic and military movements by the three superpowers of that time (Britain, France, Russia). These superpowers attempted to strengthen their alliances and were aware that Ottoman Empire is the loser of the war and it is time to divide its possessions. After many sessions of discussions and negotiations of the three countries (Britain, France, Russia) came to an agreement over the issue and secretly signed Sykes-Picot-Sazanov agreement in September, 1916. On the other hand, regarding their awareness about Kurdistan, these superpowers had full information about all the areas of Kurdistan. They got information about Kurdistan's geography, nature, economy, population and so on. The information was gathered by their undercover agents and spies who travelled a lot in Kurdistan cities and villages of that time. In addition, Kurdistan's oil was of high interest to them. Thus, these petroleum rich areas of Kurdistan and dividing them over these superpowers was in important and debatable issue to them. Furthermore, after exposing Sykes-Picot-Sazanov Agreement to the public in 1917, two parties of the agreement (Britain and France) indirectly worked on Ottoman Empire's Kurdistan and divided it into three parts. Thus, with the Qajari (Persian) Kurdistan, Kurdistan was divided into four parts. Hence, due to the importance of this topic, the researcher in this paper attempts to shed light on it. The paper consists of an introduction, two chapters and a conclusion. Chapter one is: A Briefing about Sykes-Picot-Sazanov Agreement. Chapter two: Ottoman Empire's Kurdistan in the agreement.